2018
DOI: 10.4236/jtst.2018.41002
|View full text |Cite
|
Sign up to set email alerts
|

The Experiential Analysis of Woven Fabric for Reproduction

Abstract: The aim of this article was to express the importance of this projected work in the field of present competitive textile-world as fabric manufacturing industries are competing with each other to be unique and aristocrat with their products for attaining customer's attention and increasing their significance to others. To be superior in market, research is the first priority in this perspective competing field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…Besides chemical auxiliaries and processing, uneven dyeing can also be caused by improper dyeing cycles. The temperature, nozzle pressure, and ring dye speed can cause creases, and the entanglement during the operating phase of the dye vat can lead to uneven dyeing and creases [6,7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides chemical auxiliaries and processing, uneven dyeing can also be caused by improper dyeing cycles. The temperature, nozzle pressure, and ring dye speed can cause creases, and the entanglement during the operating phase of the dye vat can lead to uneven dyeing and creases [6,7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Defeat of biodiversity, releases of greenhouse gases, and water contamination are all issues usually known as sustainability contests. 43 Though, issues nearby the environment establish a very significant feature of sustainability. Consequently, when thoughtful about how to extent and communicate clothing sustainability, we must be cautious not to focus exclusively on sustainability as it narrates to environmental matters.…”
Section: Textiles and Clothing Manufacturing Countriesmentioning
confidence: 99%
“…Procedures within the supply chain necessitate large water and energy inputs and comprise the use of toxic substances in the production of properties. 49 The removal of these harmful substances and other wildernesses are also environmental anxieties relevant to the diligence. Textile industry is booming and increasing at high speed expertise.…”
Section: Textiles and Clothing Manufacturing Countriesmentioning
confidence: 99%
“…Shariful et al 18 conducted some experimental analysis of woven fabrics. They reported that fibers, yarns and fabrics have so many properties and these all properties are directly or indirectly modify the shrinkage properties of fabrics.…”
Section: Introductionmentioning
confidence: 99%